The valorization of economic assets and social capacities of the historic farmhouse system in peri-urban allocation: A sample of application of the Corporate Social Responsible (CSR) approach. - Coscia, Cristina; Russo, Valentina (Springer, 2018)
Nowadays the strategies underlying agricultural and environmental policies (the Lisbon strategy 'EU 2020') - in particular the Sixth Environment Action Programme 2010: Our Future, Our Choice - emphasize the need to create a market that is more environmentally friendly and 'responsible'. The recent debate shows that the 'green' variable in financial management is placed at the center of employers' thoughts on both the discretionary dimension (culture, ethics and responsibility) and the normative-prescriptive dimension. Some positive experiences reveal the following topics: (1) the approaches of multifunctional agriculture in synergy with the themes of the European debate on Corporate Social Responsibility; (2) the definition of a new business framework; and (3) the management model oriented to stakeholders and to ethical management. The vision of the green entrepreneur in managing the company is an innovative point of view with respect to legal obligations and falls within the sphere of responsibility for environmental management. The literature, in fact, focuses on: (1) a responsible business-management model based on the 'stakeholder' model, as opposed to the 'shareholder model', where the creation of value is not confined to equity holders of risk, but in which companies assume management objectives that bring mutual benefit to the community; and (2) the development of specific items in the analysis of financial statements that take into account aspects of environmental responsibility. In accord with this, the paper analyzes the application of the principles of the 'responsible' management process to an Italian case study and to underline which effects they have on the scenario of enhancement of the historical farmhouse system in Volpiano (Canavese, in the metropolitan region of Turin, Italy). The coexistence of historic rural settlement patterns and new housing and industrial estates is rather common and widespread, but this case is paradigmatic, because in the territory of Volpiano the applied measures and principles followed a paradigm change in dealing with this historic farmhouse structures coexisting among new housing and industrial estates: this is an issue of great importance and not only at the local level. In fact, the final project scenario was subject to operational feasibility analysis using traditional instruments. Some specific reflections were made to estimate the financial investment for restoration and re-functioning, on the timing of site preparation and management data, and on the identification of financing channels (PSR-Programma di Sviluppo Rurale and the European CAP-Common Agricultural Policy). Lastly, feasibility is linked to the economic social responsibility, with elements of originality in the test performance and new assumptions concerning the risk/return ratio.
Keywords: Agrarpolitik; Wirtschaftsentwicklung; Dorfgestalt; Investition; Nachhaltige Entwicklung; Unternehmenskonzept; Drei-Säulen-Modell